2008
DOI: 10.1002/ptr.2400
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on theRosa canina effect and efficacy profiles

Abstract: Rose hip, rose hip and seed and rose hip seed, all were negatively monographed by the German Commission E due to insufficient evidence of effects and effectiveness. Therefore a comprehensive review of the literature was conducted to summarize the pharmacological and clinical effects of Rosa canina L. to reevaluate its usefulness in traditional medicine. For various preparations of rose hip and rose hip and seed, antioxidative and antiinflammatory effects have been demonstrated. Lipophilic constituents are invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
71
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(71 citation statements)
references
References 42 publications
0
71
0
Order By: Relevance
“…tadic et al (58) reported the anti-inflammatory, gastroprotective, free-radicalscavenging and antimicrobial activities of ethanolic extracts of hawthorn berries mixture (C. monogyna and C. oxycantha). Dog rose (Rosa canina) has astringent, aperient, stomachic, carminative, diuretic, laxative, ophthalmic, anti-inflammatory and tonic activities (11,12). Fruits have been used in folk medicine in the treatment of colds, influenza, minor infectious diseases, scurvy, diarrhea and gastritis (7,11,22).…”
Section: Introductionmentioning
confidence: 99%
“…tadic et al (58) reported the anti-inflammatory, gastroprotective, free-radicalscavenging and antimicrobial activities of ethanolic extracts of hawthorn berries mixture (C. monogyna and C. oxycantha). Dog rose (Rosa canina) has astringent, aperient, stomachic, carminative, diuretic, laxative, ophthalmic, anti-inflammatory and tonic activities (11,12). Fruits have been used in folk medicine in the treatment of colds, influenza, minor infectious diseases, scurvy, diarrhea and gastritis (7,11,22).…”
Section: Introductionmentioning
confidence: 99%
“…In Europe and America, rosehip is processed widely into jam and juice, used as a vitamin C supplement, in cosmetics, and as a folklore drug in the form of tisane 4,5. The functional capacities of rosehip includes efficacy on diuresis, as a laxative, and as treatments for gout and rheumatism 6,7. There have also been reports of several effects including antioxidative,8 anticold, and anti-inflammatory actions,9 inhibitory effects on metabolism of arachidonic acid and formation of cyclooxygenase 1, cyclooxygenase 2, and leukotriene B4,10 suppression of inflammation and cancer cell proliferation attributable to anticomplementary effect,11 antibacterial action and suppression of experimental nephrolithiasis,12 melanin production inhibition,13 and antidiarrheal action using a methanol extract of rosehip leaves 14.…”
Section: Introductionmentioning
confidence: 99%
“…Rose hip is the pseudofruit of the rose plant. 6 The fruit is rich in antioxidants, such as ascorbic acid, phenolic compounds and carotenoids. It has been used in traditional medicine for almost a century for its high content of ascorbic acid.…”
Section: Introductionmentioning
confidence: 99%